Fiction in the construction of characters and temporal and spatial dimensions in “Where and how the devil lost the poncho ” - Vásquez Peña, José Carlos (2019)
Taking as a model the tradition “Dónde y cómo el diablo perdió el poncho”, the style of Palma is analyzed, under the narratological approach, focusing on the following elements of literary creation: construction of characters and handling of the temporal and spatial dimensions, without leaving aside the aspectual dimension contained in the theme and the circumstances produced after the unrealisation process operated in the text. This balance shows Palma’s extraordinary creative capacity to fictionalize stories, to show us, in this case, a textual Ica that, without leaving its landscape essence and the idiosyncrasy of its characters, becomes another Ica, which houses protagonists and antagonists in an unprecedented spatiotemporal dimension.